Determining the Effect of Alccofine and GGBS Addition on the Durability of Cement Concrete - R, Balamuralikrishnan; Saravanan J (Current Approaches in Engineering Research and Technology Vol. 6, 2024)
The durability of cement concrete is well defined as its ability to resist weathering action, chemical attack, or any other process of deterioration. Durable concrete will hold its original form quality, and serviceability when exposed to the environment. The primary component of concrete is Portland cement. Large-scale cement production facilities use a lot of energy and generate a lot of unwanted products (CO2), which harm the environment and deplete natural resources. This threat to ecology has led researchers to use industrial by-products as a supplementary cementitious material in making concrete. In view of this silica fume (SF), ground granulated blast furnace slag (GGBS), rice husk ash, fly ash (FL), metakolin, alccofine (AL), micro-fine material, etc.; are tried out for replacing cement partially or fully in concrete, without compromising on its strength, also reduce greenhouse gases and sustainable way of management of waste. Alccofine is a specially processed product based on slag of glass content with high reactivity obtained through the process of granulation. A new ultra-fine material that emerged in the market is called Alccofine. This is available as a cementitious material for replacing cement. Since this is a new material, a study is tried out with the combination of Alccofine and GGBS. Ordinary Portland Cement 53 grade was used throughout the study and the grade of concrete is M20. Totally 108 cubes and 27 cylinders were cast and tested in the laboratory with nine different percentage combinations of Alccofine (A), GGBS (G) and cement (C) (C100, C70A0G30, C90A10G0, C60A10G30, C30A10G30, C40A0G60, C85A15G0, C55A15G30, C25A15G60). The average loss of weight and loss of compressive strength is considerably low. As the attack proceeds, all the cement compounds are evenly broken and leached away, together with carbonate aggregate material. In each case, 3 nos. of specimens were used for repeatability. It is intended to study the compressive strength, and its durability properties like acid attack test, sulphate attack test and rapid chloride permeability test (RCPT). Among the nine different combinations, the maximum compressive strength of concrete is achieved by using AL10% and GGBS 30% is 38.08 N/mm2. C60A10G30 is 28.76% higher than the control mix. The result shows that concrete incorporating alccofine and GGBS have higher compressive strength and alccofine enhanced the durability of concrete also. It is recommended to utilize the AL material with cement after checking its other durability properties and flexural studies on beams.